Influence of Sociodemographic Factors on the Social Development and Self-Esteem of Adolescents: A Comparative Study of Single and Two-Parent Households - Dr. Asma Seemi Malik; Dr. Nayab Javed; Amjad Mahmood (Journal of Management Practices, Humanities and Social Sciences, 2022)
The focus of this study was to examine the influence of sociodemographic factors such as age, education, siblings’ number, family income, and family systems on the social development and self-esteem of the adolescents of a single parent or both parents and how the absence of both parents can influence these important aspects. It is a quantitative cross-sectional research design with the survey as a method. Adolescents from single and from both parents, male, and female (N=320), 160 from single-parent families, and 160 from two-parent families took part in the field survey on self-esteem. Heatherton and Polivy (1991) state self-esteem scales were used to collect data. Data were verified with SPSS version 21.0. A significant difference was visible in adolescents’ self-esteem with both parents compared to adolescents with a single parent. A weak correlation was found between age, education, and self-esteem. For siblings’ number, it was found that adolescents of intact families, were more statistically associated than adolescents with a single parent regarding the number of siblings. Outcomes confirm the approach of a strong family system to strengthen the functioning of intact families by emphasizing the joint and extended family connections that only contribute to boosting the spousal relationship, paternal and maternal grandparents, and grandchildren relationships. Clinicians and educators working with step families should promote positive, emotionally close step relationships and encourage strong marital bonds and trust in higher-order marriages.